Hubungan Kepemimpinan, Disiplin Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan di PT. Lima Dara Balikpapan - Muhamad Noval; Didik Hadiyatno; Rahajeng Cahyaning Putri Cipto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to find out the Influence of Leadership, Work Discipline, and Employee Work Environment at PT. Lima Dara Balikpapan. The type of research used is Quantitative research. The sampling technique in this study is saturated/census sampling with a sample of 50 employees of PT.Lima Dara Balikpapan. The data collection method was carried out by distributing questionnaires. This study uses SmartPLS in managing data. The results of this study show that leadership variables have a positive and significant effect on employee job satisfaction at PT. Lima Dara Balikpapan, the Work Discipline variable has a positive and significant effect on employee job satisfaction at PT. Lima Dara Balikpapan, and the variables of the Work Environment have a positive and significant effect on job satisfaction at PT. Lima Dara Balikpapan.